Pengaruh Investment Opportunity Set (IOS), Struktur Modal, Kepemilikan Manajerial dan Pertumbuhan Penjualan terhadap Nilai Perusahaan - Irfansah, Nur; Fitri, Yessi (Faculty of Economics and Business, 2025)
This study aims to examine the effect of the Investment Opportunity Set (IOS), capital structure, managerial ownership, and sales growth on firm value in manufacturing companies listed on the IDX during 2022–2024. Using purposive sampling, 31 companies were selected, yielding 93 observations. Variables include IOS (CAPBVA), capital structure (DER), managerial ownership, and sales growth, with firm value measured by PBV. Panel data regression with Eviews12 shows that capital structure and sales growth significantly and positively affect firm value, while IOS and managerial ownership show no significant effect.